2013
DOI: 10.1063/1.4793538
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin light scattering spectra as local temperature sensors for thermal magnons and acoustic phonons

Abstract: We demonstrate the use of the micro-Brillouin light scattering (micro-BLS) technique as a local temperature sensor for magnons in a Permalloy (Py) thin film and phonons in the glass substrate.When the Py film is uniformly heated, we observe a systematic shift in the frequencies of two thermally excited perpendicular standing spin wave modes. Fitting the temperature dependent magnon spectra allows us to achieve a temperature resolution better than 2.5 K. In addition, we demonstrate that the micro-BLS spectra ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…This is accompanied by a flow of balancing spin current that diffuses towards (away from) the hot (cold) end of FM/NM (say Pt) interface, which, if electrical detection is used results in a linear asymmetrical spatial dependence of the ISHE signal in the Pt overlayer [4]. If the Sagnac MOKE only senses the magnetization distribution in the NiFe film (represented by the T (x) profile), then according to the 'phonon-magnon drag' model the measured T (x) slope should be similar or slightly smaller than that of the phonon temperature profile T (x), similar to that inferred using the BLS method [22,23]. However this is opposite to what we observed in Figs.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This is accompanied by a flow of balancing spin current that diffuses towards (away from) the hot (cold) end of FM/NM (say Pt) interface, which, if electrical detection is used results in a linear asymmetrical spatial dependence of the ISHE signal in the Pt overlayer [4]. If the Sagnac MOKE only senses the magnetization distribution in the NiFe film (represented by the T (x) profile), then according to the 'phonon-magnon drag' model the measured T (x) slope should be similar or slightly smaller than that of the phonon temperature profile T (x), similar to that inferred using the BLS method [22,23]. However this is opposite to what we observed in Figs.…”
mentioning
confidence: 97%
“…In principle, optical spectroscopy such as micro-Brillouin light scattering (BLS) offers an elegant non-contact measurement method for investigating the spatial difference between the thermally activated magnon and phonon populations in a magnetic system [22,23], which is considered to be the underlying mechanism accounting for the SSE (dubbed 'phonon-magnon drag' effect) [24][25][26][27][28]. However, the present BLS resolution for sensing magnon/phonon temperature difference that results from a limited thermal gradient in the FM still cannot provide direct evidence in support of this model [22,23].…”
mentioning
confidence: 99%
“…The BLS spectra are generally characterized by three parameters: frequency, linewidth, and integrated intensity (further referred to simply as intensity). Previous BLS experiments have solely used the frequency shift to determine the temperature of magnons 11,19 . In a different study, it was shown that frequency shift, linewidth, and intensity of BLS spectra of acoustic phonons in silicon all provide temperature sensing capabilities, though each probes different ranges of the acoustic phonon spectrum 16 .…”
mentioning
confidence: 99%
“…The Curie temperatures of these materials are 560 K for YIG, and 550K to 870K for Py depending on the crystal structure 20,21 . BLS spectra are collected using a µBLS system, briefly described as follows 12,19,22 . A single frequency, linearly polarized 532 nm laser beam, normally incident on the sample, is focused using an objective lens (NA 0.70) to a spot size of approximately 1 µm in diameter.…”
mentioning
confidence: 99%
“…32,33 Recently, Brillouin light scattering (BLS) techniques have been used as a local temperature sensor for magnons in metallic and insulating ferromagnetic materials and for low-frequency phonons in glass. 34,35 However, the application of this thermometry method for acoustic phonons in semiconductors remains to be investigated.…”
mentioning
confidence: 99%